Design and Test of Multifunctional Vegetable Transplanting Machine. Issue 30 (2019) - Shao, Yuanyuan; Liu, Yi; Xuan, Guantao; Hu, Zhichao; Han, Xiang; Wang, Yongxian; Chen, Bin; Wang, Weiyang
Abstract: In order to improve the efficiency of vegetable seedling transplantation and realize its high quality transplanting, this paper developed a multi-functional vegetable pot seedling transplanting machine. The machine was mainly composed of duckbill type planter, fertilization mechanism, power transmission system, soil covering device, watering device, film covering and pipe laying mechanism, etc. It could perform drip irrigation tape laying and film covering, transplanting, fertilizing, soil covering, watering and other working procedures at one time. In order to evaluate the work performance of the machine, field tests were conducted with 35 day-old pepper and tomato seedlings as testable subjects. The results showed that when the planting frequency were 57, 72 and 88 seedlings/min, the seedling-standing ratio decreased slightly with the increase of planting frequency, the average values were 96.4% 98.6%. The coefficient of variation of seedling spacing and the mechanical damage degree of plastic film increased with average values of 1.6% 6% and 3.8 7.9 mm/m 2 respectively. The average values of the qualified rate of planting depth were 97.2% 99.0%. Seedling-standing ratio and mechanical damage degree of plastic film of diamond duckbill type planter were better than flat duckbill type planter. The test results met the requirements of mechanical industry standards. The field test results were basically consistent with the ADAMS simulation results. The structure of the transplanter was reasonable and the performance was stable. The watering device, covering device, film covering and pipe laying mechanism of the transplanter were coordinated, which could carried out the functions of each part accurately and met the agronomic requirements of vegetable seedling transplantation.